Housekeeping Housekeeping Development For Homestay Managers In Kampung Purba Tourism Village, Dayu, Gondangrejo Karanganyar - Ichwan Prastowo; Resmi Prastiwi Citra (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2022)
The implementation of this community service is to foster Homestay managers in the tourist village of Kampung Purba Dayu, Karanganyar Regency in growing and developing homestays by providing knowledge and skills to all related people in order to create professional homestay human resources. This housekeeping development method is with theory and practice that is adapted to the conditions of the homestay that already exists in the homestay. The results obtained from the coaching participants are getting a job description and standard operating procedures as work guidelines, having skills in the field of housekeeping and being able to apply everything they get in carrying out homestay operations.